Multidisciplinary management of Whipple’s disease complicated with rectal stenosis from multidisciplinary nursing management: A case study - Fang Ding; Lili Dong; Yahong He; Wenli Wu; Rong Xu (Pakistan Journal of Medical Sciences, 2026)
Whipple’s disease (WD) is a rare, chronic systemic disorder caused by Tropheryma whipplei (T. whipplei), a bacterium belonging to the Actinobacteria phylum. Clinical manifestations of WD include weight loss, diarrhea, and arthralgia. To date, no cases of rectal stenosis caused by T. whipplei infection have been reported in the literature. This paper presents a case of rectal stenosis associated with T. whipplei infection, evaluates the effectiveness of comprehensive, multidisciplinary management, and provides guidelines for optimizing disease management. A 40-year-old male patient presented with a one-year history of constipation and weight loss. He reported the passage of narrow-calibre stools, approximately the width of a little finger, and a 10-kilogram weight loss over the past year. A diagnosis of WD was indicated by bronchoalveolar lavage (BAL) fluid analysis, but no microbiological evidence of rectal T. whipplei infection was found at that time. The patient received 14 days of intravenous antibiotic therapy, followed by a one-year course of oral cotrimoxazole, combined with a comprehensive management plan that included structured medication adherence education, targeted intestinal nursing care, nutritional support, psychological intervention, and multidisciplinary follow-up. After five months of treatment, the patient showed significant improvement, including four-kilogram weight gain, a return to normal bowel movements, and resolution of pulmonary inflammation. This case highlights the importance of early recognition of atypical WD manifestations and demonstrates that a multidisciplinary model integrating standardized antimicrobial therapy with structured nursing management may significantly improve patient outcomes in rare systemic infections.